A comparative study of fractional step method in its quasi-implicit, semi-implicit and fully-explicit forms for incompressible flows - Bevan, Rhodri LT; Boileau, Etienne; van Loon, Raoul; Lewis, R.W.; Nithiarasu, P (International journal of numerical methods for heat & fluid flow, 2016)
Purpose - The purpose of this paper is to describe and analyse a class of finite element fractional step methods for solving the incompressible Navier-Stokes equations. The objective is not to reproduce the extensive contributions on the subject, but to report on long-term experience with and provide a unified overview of a particular approach: the characteristic-based split method. Three procedures, the semi-implicit, quasi-implicit and fully explicit, are studied and compared. Design/methodology/approach - This work provides a thorough assessment of the accuracy and efficiency of these schemes, both for a first and second order pressure split. Findings - In transient problems, the quasi-implicit form significantly outperforms the fully explicit approach. The second order (pressure) fractional step method displays significant convergence and accuracy benefits when the quasi-implicit projection method is employed. The fully explicit method, utilising artificial compressibility and a pseudo time stepping procedure, requires no second order fractional split to achieve second order or higher accuracy. While the fully explicit form is efficient for steady state problems, due to its ability to handle local time stepping, the quasi-implicit is the best choice for transient flow calculations with time independent boundary conditions. The semi-implicit form, with its stability restrictions, is the least favoured of all the three forms for incompressible flow calculations. Originality/value - A comprehensive comparison between three versions of the CBS method is provided for the first time.